Puppies, dogs, and blue northers - Paulsen, Gary (Orlando : Scholastic, 1996)
Minnesota author and dog musher Gary Paulsen reflects on the growth of his sled dogs as he and his animals discover the world around them.
Z
1190
Z
Keywords: Mushers -- Minnesota -- Biography -- Juvenile literature; Sled dogs -- Minnesota -- Biography -- Juvenile literature; Dogsledding -- Minnesota -- Juvenile literature; Sled dogs; Dogsledding; Mushers; Outdoor life -- Minnesota; Audiobooks; Children's audiobooks